Models of the Computer Intellectualization Optimal Strategy of the Power Supply Fast-Flowing Technological Processes of the Railways Traction Substations - Stasiuk, Aleksander; Kuznetsov, Valeriy; Goncharova, Lidia; Hubskyi, Petro (Communications - Scientific Letters of the University of Zilina, 2021)
Based on analysis of the problem of the power supply networks of railways innovative transformation, the direction of research is substantiated related to organization of the optimal strategy of computerized intellectualization of the power supply processes to the railways traction substations. The logical structure of a distributed computer environment developed in the form of graph, which adequately reflects the topology of the organization of the power supply system. A differential mathematical model of the computer architecture of the power supply control is proposed. An intelligent method for finding the optimal strategy for the intellectualization of the power supply processes was proposed to guarantee the specified indicators of the optimal functioning of individual nodes and segments of the power supply management computer network.
Keywords: differential mathematical models; optimal strategy; intellectualization; power supply; optimization; minimax principle